Chemical engineering design : principles, practice, and economics of plant and process design - Towler, Gavin P. (Butterworth-Heinemann, 2013)
Chemical Engineering Design, Second Edition, deals with the application of chemical engineering principles to the design of chemical processes and equipment. Revised throughout, this edition has been specifically developed for the U.S. market.